Dapagliflozin Attenuates Hyperglycemia Related Osteoporosis in ZDF Rats by Alleviating Hypercalciuria - Wang, Ji-Yu; Cheng, Yan-Zhen; Yang, Shuang-Li; An, Min; Zhang, Hua; Chen, Hong; Yang, Li (Frontiers in Endocrinology, 2019)
Recent studies showed that SGLT2I (Sodium-dependent glucose transporters 2 inhibitor) may possess potential adverse effect on skeleton when treating type 2 diabetes mellitus (T2DM). However, whether SGLT2I aggravates osteoporosis in patients with T2DM and the particular mechanism remains controversial. In this study, we explored whether the usage of Dapagliflozin alleviated diabetic related osteoporosis in animal models. The effect of Dapagliflozin on skeleton was evaluated in male ZDF (Zucker Diabetic Fatty) rats -a rat model of diet induced spontaneous T2DM, and Dapagliflozin were administrated via gavage. Skeleton tissue mineral density and microarchitecture were measured along with serum bone biomarkers and other metabolic parameters. We found decreased cortical bone mass density after SGLT2I treatment while trabecular bone mass density and ductility received a rise. These changes in bone morphology were possibly connected to the change in hyperglycemia and ion metabolism caused by calcitonin. Our results indicating that SGLT2I may help to prevent the skeleton damage caused by diabetes. The aggravation of diabetic related osteoporosis and increased factures demonstrated by the recent clinical researches were probably the outcome of the holistic changes in diabetic individuals after administrated SGLT2I.